Luigi Ghirri - Alcune soste di Luigi Ghirri lungo la via Emilia - Bartocci, Gabriele (Firenze Architettura, 2017)
The shots of the landscape that Luigi Ghirri “constructs” during some stops along the Via Emilia represent moments of reflection on phenomena concerning the transformation of the Italian territory, the alteration of the genetic codes of a historical landscape by cities which have grown without control. Through photography the artist interrogates consciences, triggering a feeling of individual responsibility vis-à-vis the tradition that is opposed to surrendering to destiny.